How to have sex in a pandemic: the development of strategies to prevent COVID-19 transmission in sexual encounters among gay and bisexual men in Australia. Issue 3 (1st March 2023) - Murphy, Dean; Ellard, Jeanne; Maher, Lisa; Saxton, Peter; Holt, Martin; Haire, Bridget; Grulich, Andrew; Bavinton, Benjamin; Philpot, Steven; Bourne, Adam; Storer, Daniel; Jin, Fengyi; et al.
Abstract: Although many studies reported on decreases in sexual partner numbers among gay and bisexual-identifying men in the early period of the COVID-19 pandemic, few studies have explored COVID-19 risk-reduction strategies. Drawing on free-text responses in an online survey (from April to July 2020), we describe the ways in which men sought to minimise the risk of COVID-19 in sexual encounters. Partner selection was an important strategy, in particular, restricting sex to men they already knew. Accounts also indicate how participants assessed risk from potential sex partners based on symptoms, residential location, recent travel, work role, and number of other sexual contacts. Less common were in situ practices, such as avoiding kissing. Participants' responses provide insight into creative community-based responses in the early months of the pandemic, some of which have resonances with early responses to HIV. Findings are discussed in relation to the concepts of 'lay epidemiology' and 'counterpublic health'. In particular, we examine how risks and health are experienced and valued in relation to local knowledges, meanings, and practices; and how practices emerge in response to dominant public health discourses that produce an idealised public based on (hetero)normative assumptions.